Perencanaan Komunikasi Dinas Perhubungan Kota Surakarta dalam Mensosialisasikan Program Batik Solo Trans - Naufal Dzakiyul Afkar Putra; Novita Haryono (Jurnal Komunikasi Massa, 2024)
The city of Surakarta has a public transportation facility called Batik Solo Trans, initiated by the Surakarta City Government through the Department of Transportation to increase public interest in the use of public transportation. This research explains the efforts of the Surakarta Transportation Agency (Dishub) in designing and implementing the BST socialization program that has been carried out for ten years. The program is conducted regularly in schools, sub-districts, and districts, with different themes and focuses each year. This research aims to understand the communication planning of the Surakarta City Transportation Agency in socializing the Batik Solo Trans Program to increase public interest in public transportation. The method used is descriptive qualitative, focusing on gaining a deep understanding of planning, organizing, actuating, and controlling. Data collection techniques used in this study are in-depth interviews, observations, and documentation conducted in the Surakarta City environment. The results of this study indicate that the planning, organizing, actuating, and controlling processes have been implemented. The planning element attempts to see how the planning carried out by the Transportation Agency to arrange activity plans that include efforts to increase public interest in Surakarta's public transportation. The organizing stage involves the formation of a coordinated work team, with members having clear roles and responsibilities, creating an efficient structure to support program implementation. Actuating is the stage of implementing planned activities. Finally, the controlling stage includes a comprehensive evaluation of the program's effectiveness, including community responses, participation levels, and understanding of Batik Solo Trans.